Investigaciones arqueológicas en el sitio Volio Cat. UCR 179, San Ramón, Alajuela - Rojas Hernández, Patricia (2015)
Archeological research in Volio site (UCR 179) includes survery, excavation of three stratigraphic trenches, and partial exposure of an architectonic features. It is presented the results of these studies, the data is analyzed, and some interpretations aimed to explain the social and cultural development of the people who inhabited the site.